2021
DOI: 10.1021/acsami.1c08365
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Metal–Organic Layers with High Catalytic Performance toward Detoxification of a Chemical Warfare Agent Simulant

Abstract: Two-dimensional (2D) metal−organic layer (MOL) materials are highly desired against chemical warfare agents (CWAs). However, the rapid synthesis of 2DMOLs with open metal sites in a single step is very challenging. Herein, a facile bottom-up method for synthesizing MOLs with microwave assistance is applied to produce Zr/Hf-BTB MOLs, composed of six-connected M 6 O 4 (OH) 412+ and the tritopic carboxylate ligand 1,3,5-tris(4-carboxyphenyl)benzene (BTB). The synthesis and ligand exchange steps can be combined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Concentrated hydrochloric acid (HCl, 37%) possesses functions of both modulation and activation. , We adopt HCl as both a modulator and an activator to synthesize a series of defected granular Zr-MOG-X xerogels by adjusting the amount of HCl. As shown in the insets of Figure , as HCl increases, the color of macroscopic monolithic Zr-MOG-X (∼ a few millimeters) changes from brown to light yellow.…”
Section: Resultsmentioning
confidence: 99%
“…Concentrated hydrochloric acid (HCl, 37%) possesses functions of both modulation and activation. , We adopt HCl as both a modulator and an activator to synthesize a series of defected granular Zr-MOG-X xerogels by adjusting the amount of HCl. As shown in the insets of Figure , as HCl increases, the color of macroscopic monolithic Zr-MOG-X (∼ a few millimeters) changes from brown to light yellow.…”
Section: Resultsmentioning
confidence: 99%
“…S4, † the flower-shape morphology constructed with ultrathin 2D layers can be observed in the images of all the five materials, indicating that there is no morphological change after both the removal of benzoate and the installation of terbium at various temperatures; this morphology is also consistent with that of ZrBTB reported previously. 56 Representative HR-TEM images of Tb-ZrBTB-120 are shown in Fig. 3(a and b).…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Recent works have noted that the introduction of a second metal could efficiently improve the hydrolytic activity of nerve agents. ,,,,, Thus, we treated activated ZZU-282 with MCl 2 (M = Co, Ni, and Zn) in DMF to prepare three heterometallic ZZU-282-M samples (Figure a). Characterization of the obtained heterometallic ZZU-282 showed that the crystallinity and porosity remained unaltered (Figures S25 and S26).…”
Section: Resultsmentioning
confidence: 99%